2017
DOI: 10.1093/eurheartj/ehx100
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and in-hospital complications of cardiac resynchronization therapy: trends in the United States from 2003 to 2013

Abstract: From 2003 to 2013, the severity of comorbid conditions increased and a rising trend was observed in the rate of periprocedural complications among patients undergoing CRT in the United States. In-hospital mortality and length of stay showed no uniform trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Women accounted for 29.9% of all patients undergoing any type of CRT implantation, meaning that 79.2% of women received CRT-Ds compared with 87.5% of men (or, conversely, that 20.8% of women received CRT-Ps compared with 12.5% of men). The fact that >70% of all CRT devicesdand of CRT-Ds, specificallydwere implanted in men gives one pause for thought but was described in more detail in a previous report by the same authors 9 and has been observed in other studies, including in similar analyses using the NIS, 10,11 and in other countries. 12 Rather, the current analysis is focused on relative differences between the sexes in the type of CRT device implanted.…”
mentioning
confidence: 80%
“…Women accounted for 29.9% of all patients undergoing any type of CRT implantation, meaning that 79.2% of women received CRT-Ds compared with 87.5% of men (or, conversely, that 20.8% of women received CRT-Ps compared with 12.5% of men). The fact that >70% of all CRT devicesdand of CRT-Ds, specificallydwere implanted in men gives one pause for thought but was described in more detail in a previous report by the same authors 9 and has been observed in other studies, including in similar analyses using the NIS, 10,11 and in other countries. 12 Rather, the current analysis is focused on relative differences between the sexes in the type of CRT device implanted.…”
mentioning
confidence: 80%
“…The chi-square (χ2) test and Wilcoxon rank sum test were used to compare categorical variables and continuous variables, respectively. The NIS provided discharge sample weights that were calculated within each sampling stratum as the ratio of discharges in the universe to discharges in the sample (25). Prior to 2012, a 20% sample from all hospitals in the United States providing long-term acute care and 100% discharge data from these hospitals were retained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some observational studies have analyzed the utilization of CRT devices in various patient groups [77][78][79][80][81] but few have connected the utilization patterns with changes in guidelines in a wider setting [82]. One study has observed the evolution of guidelines as an underlying reason for increased pharmaceutical utilization in the US [83].…”
Section: Discussionmentioning
confidence: 99%